Densely Placed Rectenna Array With Decoupling Slots for Enhanced Received Power in Far-Field Wireless Power Transfer - Min-Seong Kim; Dong-Hwan Park; Mohamed Elhefnawy; Wang-Sang Lee (IEEE Access)
In this paper, a rectenna array system using decoupling slots with a defected ground structure (DGS) is proposed to improve received power in wireless power transfer (WPT) applications. The proposed rectenna array features a $4× 4$ configuration with an antenna spacing of $λ _{0}/3$ and introduces decoupling slots based on a meander line DGS structure between the H-plane arrays. The proposed rectenna array operates at 5.8 GHz and has dimensions of $78× 78× 0.76$ mm3. The rectenna array achieves miniaturization, enhanced gain, and the ability to receive power regardless of the antenna polarization, through the high isolation formed by the decoupling slots. For performance validation, the operating principle of the proposed rectenna array system was theoretically analyzed and simulated. Additionally, the received power was measured based on the polarization of the transmitting antenna, and the results were compared with a conventional rectenna array and a proposed rectenna array without decoupling slots, both with the same area. The measurements show that the rectenna array with decoupling slots improves the power reception in environments with polarization mismatch, compared to the conventional rectenna arrays.